Evaluation of Kecipir Seed Extract (Psophocarpus tetragonolobus L.) in Feed on the Growth Performance of Catfish (Clarias sp.) - Wicaksono, Ridho; Armando, Eric; Tartila, Shobrina Silmi Qori (JURNAL AKUAKULTURA, 2025)
Optimizing nutrient utilization and minimizing feed costs are essential for supporting fish growth, with winged bean presenting a viable solution. This study aimed to determine the optimal dosage of dietary winged bean extract supplementation to enhance the growth performance of catfish. Catfish (mean weight 7.44 ± 0.16 g) were stocked at a density of 1 fish/L in 20 L containers. A completely randomized design was utilized, comprising four treatment groups based on the dosage of winged bean seed extract: 0 ml/kg feed (P1), 10 ml/kg feed (P2), 30 ml/kg feed (P3), and 50 ml/kg feed (P4), with each treatment replicated four times. Growth performance parameters included absolute length (Pm), absolute weight (Wm), feed intake (FI), feed conversion ratio (FCR), specific growth rate (SGR), and survival rate (SR). Data were analyzed using a one-way ANOVA, followed by Duncan's Multiple Range Test at a 95% confidence level (p<0.05). Catfish fed P4 exhibited the best growth performance, with Pm of 4.32 ± 0.51 cm, Wm of 15.75 ± 2.75 g, SGR of 52.49 ± 9.18%/day, and FCR of 1.21 ± 0.09, though insignificantly different from P3. This study concluded that 50 ml/kg feed of winged bean seed extract optimally enhances catfish growth performance.